CHARACTERISTICS OF PATIENCE AMONG STUDENTS WITH DISABILITIES IN HIGHER EDUCATION: A PHENOMENOLOGICAL STUDY - Ahmad Hidayat; Annisa Putri (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This phenomenological study aims to deepen the understanding of the characteristics of patience among students with disabilities in higher education. The basis for this research lies in the Indonesian Law Number 8 of 2016 concerning Persons with Disabilities, which is further regulated by the Government Regulation of the Republic of Indonesia Number 48 of 2023, specifically addressing the provision of appropriate accommodations for students with disabilities in higher education. The qualitative phenomenological approach was employed in this study. The research objective was to explore the characteristics of patience among students with disabilities in higher education. Two students with disabilities from the Faculty of Psychology at the University of Islamic Riau were selected as the research subjects. The study revealed that the characteristics of patience among these students were related to academic resilience, self-control, resilience, and self-acceptance. For students with physical disabilities, patience was primarily associated with limitations in physical mobility, while for students with hearing impairments, patience was linked to limitations in hearing. The implications of this research emphasize the crucial need for counseling services to support and enhance the patience of students with disabilities. Furthermore, the Indonesian government must firmly enforce Law Number 8 of 2016, as it pertains to human rights, particularly for students with disabilities in higher education.